2022
DOI: 10.22270/jddt.v12i2-s.5421
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foot Exercise on Daily Activities and Blood Sugar Levels of Elderly in South Bangka, Indonesia

Abstract: Background: The elderly are a group of people who are at risk of developing diabetes mellitus. Foot exercise is appropriate for elderly people with diabetes to prevent injuries and help improve blood circulation in their feet and also could control blood sugar level. Objective: This study time to determine the effect of foot exercise on daily activities and blood sugar levels among elderly in Tanjung Ketapang Village, Toboali District, South Bangka Regency. Methods: The research employed a quasi-experimental o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Some additional benefits include supporting the improvement of patients' daily activity levels and reducing blood glucose levels. In a study by Nurhayati (2022), positive changes were observed in both aspects, and statistically, they were attributed to diabetes foot exercises.…”
Section: Outcomes Of Diabetic Foot Exercisesmentioning
confidence: 95%
See 1 more Smart Citation
“…Some additional benefits include supporting the improvement of patients' daily activity levels and reducing blood glucose levels. In a study by Nurhayati (2022), positive changes were observed in both aspects, and statistically, they were attributed to diabetes foot exercises.…”
Section: Outcomes Of Diabetic Foot Exercisesmentioning
confidence: 95%
“…High-intensity exercise frequency is associated with activity and the risk of physical functional limitations in older adults. High-certainty evidence demonstrates that balance and functional exercises reduce the rate of falls and can help improve various elements of physical function (Nurhayati, 2022).…”
Section: Outcomes Of Diabetic Foot Exercisesmentioning
confidence: 99%